2004
DOI: 10.1089/aid.2004.20.1145
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of HIV Incidence among Repeat Anonymous Testers in Catalonia, Spain

Abstract: A retrospective cohort study of 2124 repeat HIV testers attending at anonymous testing sites (ATS) of Catalonia between 1995 and 2001 registered 3273 person-years (PY) of follow-up and 76 seroconversions (incidence density of 2.32 per 100 PY; 95% CI: 1.83, 2.90). The highest HIV infection incidence was observed among heterosexual injection drug users (IDU) (9.25 per 100 PY; 95% CI: 6.77, 12.25) and the lowest was among heterosexual non-IDU (0.69 per 100 PY; 95% CI: 0.35, 1.24). In multivariate Cox regression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…These findings are consistent with previous studies in London (Leaity et al, 2000;Norton et al, 1997), Catalonia (Nascimento et al, 2004) and Ontario (Ryder et al, 2005), which found that repeat VCT acceptors were less likely to change their sexual behaviors following repeat VCT. In the Ontario study, most HIV-negative repeat testers described their sexual behavior and their perception of what constitutes risky sexual behavior as unchanged following repeat HIV-negative tests and some participants believed that the repeat negative test confirmed that their current sexual behavior, such as sex without a condom, was safe.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are consistent with previous studies in London (Leaity et al, 2000;Norton et al, 1997), Catalonia (Nascimento et al, 2004) and Ontario (Ryder et al, 2005), which found that repeat VCT acceptors were less likely to change their sexual behaviors following repeat VCT. In the Ontario study, most HIV-negative repeat testers described their sexual behavior and their perception of what constitutes risky sexual behavior as unchanged following repeat HIV-negative tests and some participants believed that the repeat negative test confirmed that their current sexual behavior, such as sex without a condom, was safe.…”
Section: Discussionsupporting
confidence: 92%
“…Collectively, these findings re-affirm reports from other studies (Fisher et al, 2002;Kellogg et al, 2001), suggesting that HIV-negative testers who seek repeated counseling and testing services are also more likely to have high rates of HIV acquisition (Fernyak et al, 2002). However, while these findings provide us with a clear understanding of risk behaviors and HIV acquisition rates in HIV-negative testers who accept repeat testing, majority of these studies were conducted in Europe (Leaity et al, 2000;Nascimento et al, 2004;Norton et al, 1997;Suligoi et al, 1999) or the United States of America (Kalichman et al, 1997;Kellogg et al, 2001;MacKellar et al, 2002), and among high-risk groups such as men who have sex with men (MSM), persons presenting with STDs, or injection drug users (IDU). It is likely that these studies may not provide a complete description of the patterns of sexual risk-taking behaviors and HIV acquisition rates in repeat HIV-negative testers in the general population or in populations where these high-risk sexual practices are less prevalent, as in much of Africa (Wawer et al, 2005a).…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation